HUBUNGAN MINAT MEMBACA BUKU TEKS, KEMANDIRIAN BELAJAR, DAN HASIL BELAJAR KOGNITIF PEMBELAJARAN SEJARAH - Mega Tri Lestari; Musa Pelu; Nur Fatah Abidin (Jurnal Pendidikan Sejarah Indonesia, 2022)
This article aims to analyze the relationship between reading interest of textbooks, independence of learning, and cognitive learning outcomes of students in history learning. The ex-post facto based on the quantitative approach was used as the research method. The population in this research was eleventh-grade students in State Senior High School Kebakkramat with a total sample of 78 students taken by simple random sampling. Data collection techniques were questionnaires and documents. The results of the research showed that (1) there was a positive and significant relationship between reading interest and students' historical cognitive learning outcomes; (2) there was a positive and significant relationship between learning independence and students' historical cognitive learning outcomes; and (3) there was a relationship between reading interest and learning independence simultaneously with students' historical cognitive learning outcomes. Based on the results, it can be pointed out that the reading interest and independence should be improved through appropriate learning sources and models to enhance students' cognitive learning outcomes.  Artikel ini bertujuan untuk menganalisis hubungan antara minat baca buku teks, kemandirian belajar, dan hasil belajar kognitif siswa pada pembelajaran sejarah. Metode penelitian yang digunakan adalah ex-post facto dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah siswa kelas XI SMA Negeri Kebakkramat dengan jumlah sampel 78 siswa yang diambil secara simple random sampling. Teknik pengumpulan data adalah angket dan dokumen. Hasil penelitian menunjukkan bahwa (1) terdapat hubungan yang positif dan signifikan antara minat baca dengan hasil belajar kognitif sejarah siswa; (2) terdapat hubungan yang positif dan signifikan antara kemandirian belajar dengan hasil belajar kognitif sejarah siswa; dan (3) ada hubungan antara minat baca dan kemandirian belajar secara simultan dengan hasil belajar kognitif sejarah siswa. Berdasarkan hasil penelitian, dapat dikemukakan bahwa minat dan kemandirian membaca perlu ditingkatkan melalui sumber dan model pembelajaran yang sesuai untuk meningkatkan hasil belajar kognitif siswa.